Real-time Digital Signal Processing for Software-defined Optical Transmitters and Receivers - Schmogrow, Rene Marcel (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2014)
A software-defined optical Tx is designed and demonstrated generating signals with various formats and pulse-shapes in real-time. Special pulse-shapes such as OFDM or Nyquist signaling were utilized resulting in a highly efficient usage of the available fiber channel bandwidth. This was achieved by parallel data processing with high-end FPGAs. Furthermore, highly efficient Rx algorithms for carrier and timing recovery as well as for polarization demultiplexing were developed and investigated.